FORMATION OF MOTHER LANGUAGE COMPETENCES OF PRIMARY CLASS TEACHERS IN THE PROCESS OF PROFESSIONAL IMPROVEMENT (Web of Teachers: Inderscience Research, 2024)
The article talks about the formation of competences of primary school teachers in the subject of mother tongue in the process of professional development.